ANALYSIS OF AFFECTING FACTORS ON PURCHASE DECISION OF SPORT SHOES "FAKE PRODUCT" OF GOLD'S GYM CONSUMERS IN WEST JAKARTA - Catur Widayati, Christina; Sinambela, Sarton; Magito, Magito; Ikhsani, Khilyatin (Dinasti International Journal of Management Science, 2021)
The purpose of this study is to find out the factors which affect on purchase decision of fake (non-genuine) Nike sports shoes. Data analysis generally confirms the structural relationship of all variables, namely price and country of origin on brand image and its impact on purchase decision for fake (non-genuine) Nike shoes. This research was conducted on Gold's Gym consumers in the city area of ??West Jakarta with a sample size of 130 respondents. The data analysis method used in this study is the Component or Variance Based Structural Equation Model where the data processing used Partial Least Square (Smart-PLS) version 3.2.9. The results show that all hypotheses can be accepted, except for the third hypothesis, which indicates that the country of origin does not effect on purchase decision.